Spatial analysis of crime and identification of clusters in the province of Trujillo (SCIÉNDO INGENIUM, 2021)
The analysis and identification of geographical areas with the highest incidence of crime can be useful in decision-making, especially for professionals involved in crime prevention, as well as for the development of preventive policies against crime. The main objective of this work is to analyze and identify the most recurrent crimes in the province of Trujillo, during the period 2015-2018, and determine the existence of spatial clusters with high values, in order to locate districts with high risk. The degree of spatial association between districts was calculated using the global Moran index, with a significance level of 5%, and the spatial clusters were identified using the local Moran and Getis-Ord indicators. Finally, the results showed that the crime rate has been increasing periodically, and local indicators evidenced the existence of spatial agglomerations of districts with high values in different areas of the province, for the specific crimes of theft, robbery, common danger and extortion.
Keywords: crime; specific crimes; districts; clusters; spatial autocorrelation